The effects of salmeterol on power output in nonasthmatic athletes - McDowell, S. L.; Fleck, S. J.; Storms, W. W. (The Journal of Allergy and Clinical Immunology, 1997)
BACKGROUND: Salmeterol xinafoate is a new aerosol inhalant that is used in the treatment of asthma. It is currently banned by the International Olympic Committee because of the concern that it may lend an unfair competitive advantage to the user. OBJECTIVE: The purpose of this study was to determine whether salmeterol improves short-term anaerobic performance in elite nonasthmatic track cyclists. METHODS: Eleven elite track cyclists volunteered to perform a 30-second all-out cycle ergometer test 3 hours after receiving either 42 micrograms of salmeterol xinafoate or placebo applied in a double-blind crossover procedure. During the ergometer test, peak power output, total work, time to peak power, and percent fatigue (decline in power output) were measured. Pulmonary measurements were also taken before and at various time points after inhalation and the ergometer test. A methacholine challenge was administered to each subject before participation in the study to ensure that none of the subjects had any reactive airway diseases. RESULTS: There were no significant differences (p > 0.05) between the placebo and salmeterol trials for peak power output, total work performed during the 30-second test, percent fatigue, and time to peak power. No differences between trials were observed for the pulmonary function test variables at any of the time points. Blood lactate concentrations before and after administration of drug or placebo were also not significantly different between trials. Additionally, salmeterol did not affect the maximal heart rate achieved during the test as compared with the placebo. CONCLUSIONS: Short-term salmeterol use within the prescribed dosage was not shown to increase short-term power output in nonasthmatic cyclists. siehe auch: http://www.ncbi.nlm.nih.gov/entrez/query.fcgi?cmd=Retrieve&db=PubMed&list_uids=7657418&dopt=Abstract